RESPONSES OF PLASMA TRANSAMINASE ACTIVITY IN CYPRINUS CARPIO VAR. COMMUNIS TO MERCURY TOXICITY - Sampath, Hannah; Ramesh, M.; Manavalaramanujam, Manavalaramanujam (Journal of Indian Fisheries Association, 2015)
The present study reports the behavioural and enzymological responsesin a freshwater teleost fish, Cyprinus carpio var. communis, exposed to acuteand sublethal toxicities of mercuric chloride. During acute treatement,significant behavioural changes like erratic swimming, excess mucus secretion,increased opercular movements, etc. were noticed. During acute ~and sublethaltreatments, both aspartate amino transferase and alanine amino transferaseactivity increased throughout the study period. Comparing the treatments,the changes in enzyme activities were found high in acute treatement and allthe values were significant at 5% level. The above findings can be used asnon-specific biomarkers of environmental pollutants.Keywords: Mercuric chloride, AST, ALT, Cyprinus carpio